Analysis of a Stadium Structure under Dynamic Loading Using Analysis Tool a Review - Sunil Kumar Yadav; Rahul Kumar Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2025)
This study provides a comprehensive analysis of the design of a multifunctional stadium constructed of reinforced concrete (RCC) using STAAD.Pro software. The primary focus is on how the structure behaves under various stresses, including seismic, wind, dead, and live loads. The stadium’s geometry and material properties were modeled using STAAD. The primary focus is on wind and seismic loads and how they impact the structural behavior of the stadium. STAAD.Pro was used to model a 21-meter stadium structure, including all of the material properties, boundary conditions, and intricate geometry. A wind analysis was conducted using IS 875:1987 Part II, accounting for varying wind speeds and directions. Seismic analysis was conducted using IS 1893:2015, accounting for the site’s particular characteristics and the risk of earthquakes.